2010
DOI: 10.1002/ptr.2926
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid protects RINm5F β‐cells from glucolipotoxicity by its antiapoptotic and insulin‐secretagogue actions

Abstract: Gallic acid is claimed to possess antioxidant, antiinflammatory and cytoprotective effects. Since pancreatic islets from Type 2 diabetic patients have functional defects, it was hypothesized that glucolipotoxicity might induce apoptosis in beta-cells and gallic acid could offer protection. To test this, RINm5F beta-cells were exposed to high glucose (25 microM) or palmitate (500 microM) or a combination of both for 24 h in the presence and absence of gallic acid. Cells subjected to glucolipotoxicity in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 40 publications
(38 reference statements)
2
46
0
2
Order By: Relevance
“…The GA, isolated from Terminalia bellerica fruit, treatment in diabetic rats showed significant antidiabetic activity [27]. GA-mediated glucose transporter 4 (GLUT4) translocation, glucose uptake in adipocyte cells, and insulin secretagogue actions in pancreatic cells were reported [28, 29]. In present study, insulin sensitization assay, incubation of AETPB and GA enhances glucose uptake in skeletal muscle cells which confirmed that GA possibly mediate the antidiabetic activity of AETPB.…”
Section: Discussionsupporting
confidence: 79%
“…The GA, isolated from Terminalia bellerica fruit, treatment in diabetic rats showed significant antidiabetic activity [27]. GA-mediated glucose transporter 4 (GLUT4) translocation, glucose uptake in adipocyte cells, and insulin secretagogue actions in pancreatic cells were reported [28, 29]. In present study, insulin sensitization assay, incubation of AETPB and GA enhances glucose uptake in skeletal muscle cells which confirmed that GA possibly mediate the antidiabetic activity of AETPB.…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have proven the significant antidiabetic effects and cardioprotective effects of gallic acid. Gallic acid increases GLUT4 translocation and cellular glucose uptake [16] prevents diabetes-induced cardiac dysfunction and causes significant decrease in the malonaldehyde, an indicator of lipid peroxidation in STZ-diabetic rats [17], and protects RINm5F beta-cells from glucolipotoxicity by its antiapoptotic and insulin-secretagogue actions [18]. Umbelliferone (UMB), also known as 7-hydroxycoumarin, hydrangine, skimmetine, and beta-umbelliferone, belongs to the coumarin family.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, non-galloyl ester catechins and GA were found to have marked antioxidant effects, which may exert synergistically beneficial health effects to ameliorate metabolic diseases such as diabetes mellitus [33]. In this context, the present findings lead us to propose that a greater population of the L. plantarum strain with high tannase activity would degrade macromolecular complexes of catechin galloyl esters and dietary proteins to release more non-galloyl ester catechins and GA in the human host intestine.…”
Section: Discussionmentioning
confidence: 86%